Beöthy et l'Avant-Garde Hongroise. (Paris : Galerie Franka Berndt, 1985)
Beöthy-Steiner, Anna ; Bortnyik, Sandor ; Czobel, Bela ; Forbat, Alfred ; Gadanyi, Jenö ; Kandar, Béla ; Kassak, Lajos ; Janos, Kmetty ; Teutsch, Mattis ; Moholy-Nagy, Laszlo ; Molnar, Farkas ; Nesmes-Lamperth, Jozsef ; Peterdi, Gabor ; REth, Alfred ; Rippl-Ronaï, Josef ; etc.
Beöthy et l'Avant-Garde Hongroise, Galerie Franka Berndt, Paris, 13 novembre 1985 au 7 janvier 1986
boek
Keywords: Beöthy, Etienne; Hongarije